(untitled) (Fiep Bulletin - online, 2017)
The Sports content in physical education classes must allow ample space for discussion in order to understand itseducational role from the understanding of sport as a cultural phenomenon. The objective of the present study was to analyze thestudents ’ perceptions of the State of Mato Grosso, network of the city of Cáceres, on the content of the sport, handball andvolleyball in EF. Participated in the study 30 students of both sexes, of three State schools of elementary and high school in thecity of Cáceres/MT as an instrument of data collection, a semi-structured questionnaire was employed with open and closedissues. The results showed that the practice of futsal if did I jump off to other sports in school. The handball was not pointed to byany student as a practice during class, while the volleyball pointed to by a small number of individuals had their practiceassociated with the training. Finally we believe that it is still necessary to improve many classes of EF. For this it is essential toinvest in the training of teachers so that they can use the infinite possibilities of existing sports in order to encourage theparticipation of all.